Synthesis and Optical Properties of Single‐Crystalline Phosphors Gd3In2Ga3O12:RE3+ (RE = Nd3+ and Ho3+) Grown via the Optical Float Zone Method - Hasan Yilmaz; Gülsüm Kinik; Masahiko Isobe; Pascal Puphal; Markus Suta; Oliver Clemens (Advanced Photonics Research)
The continuous development of innovative optical materials with lanthanoid ions as activators has emerged as a modern sector of materials chemistry. The experience with the fabrication of single crystals with the optical float zone has motivated one to investigate the luminescence of Nd3+ and Ho3+ ions in the garnets (Gd3−xREx)In2Ga3O12 (RE = Nd and Ho, x = 0; 0.15–0.30). Upon usage of an Ar/O2 (80:20 ratio) atmosphere and application of an auxiliary pressure (6 bar) to suppress In2O3 evaporation, single‐crystalline domain sizes in the order of ≈6 × 6 × 1 mm3 are obtained. Structural analysis confirms the formation of a cubic garnet phase with space group Ia3¯d, with the substituents incorporated in accordance with Vegard's law. Backscattered electron imaging and energy‐dispersive X‐ray spectroscopy are conducted, demonstrating a homogeneous elemental distribution within the crystals. Photoluminescence studies are carried out, revealing the characteristic narrow‐line 4f n → 4f n transitions of Nd3+ and Ho3+, with decay times in the submillisecond range, suggesting non‐negligible cross‐relaxation effects are present. Despite this, the large nearest‐neighbor Gd–Gd distance (3.88 Å) in Gd3In2Ga3O12 and the low phonon cutoff energy (≈700 cm−1) are found to limit cross‐relaxation pathways, preserving significant photoluminescence brightness. These results highlight the potential of Gd3In2Ga3O12:RE3+ single crystals as promising candidates for advanced optical applications.